Power Dynamics in Community-Based Participatory Research: A Multiple–Case Study Analysis of Partnering Contexts, Histories, and Practices. (October 2019) - Wallerstein, Nina; Muhammad, Michael; Sanchez-Youngman, Shannon; Rodriguez Espinosa, Patricia; Avila, Magdalena; Baker, Elizabeth A.; Barnett, Steven; Belone, Lorenda; Golub, Maxine; Lucero, Julie; Mahdi, Ihsan; Noyes, Emma; et al.
Community-based participatory research has a long-term commitment to principles of equity and justice with decades of research showcasing the added value of power-sharing and participatory involvement of community members for achieving health, community capacity, policy, and social justice outcomes. Missing, however, has been a clear articulation of how power operates within partnership practices and the impact of these practices on outcomes. The National Institutes of Health–funded Research for Improved Health study (2009-2013), having surveyed 200 partnerships, then conducted seven in-depth case studies to better understand which partnership practices can best build from community histories of organizing to address inequities. The diverse case studies represented multiple ethnic–racial and other marginalized populations, health issues, and urban and rural areas and regions. Cross-cutting analyses of the qualitative results focus on how oppressive and emancipatory forms of power operate within partnerships in response to oppressive conditions or emancipatory histories of advocacy within communities. The analysis of power was conducted within each of the four domains of the community-based participatory research conceptual model, starting from how contexts shape partnering processes to impact short-term intervention and research outputs, and contribute to outcomes. Similarities and differences in how partnerships leveraged and addressed their unique contexts and histories are presented, with both structural and relational practices that intentionally addressed power relations. These results demonstrate how community members draw from their resilience and strengths to combat histories of injustice and oppression, using partnership principles and practices toward multilevel outcomes that honor community knowledge and leadership, and seek shared power, policy, and community transformation changes, thereby advancing health equity.